Pannexin 1 Is Critically Involved in Feedback from Horizontal Cells to Cones - Cenedese, Valentina; de Graaff, Wim; Csikós, Tamás; Poovayya, Mitali; Zoidl, Georg; Kamermans, Maarten (Frontiers in Molecular Neuroscience, 2017)
Retinal horizontal cells feed back negatively to cone photoreceptors and in that way generate the center/surround organization of bipolar cell receptive fields. The mechanism by which horizontal cells inhibit photoreceptors is a matter of debate. General consensus exists that horizontal cell activity leads to the modulation of the cone Ca-current. This modulation has two components, one fast and the other slow. Several mechanisms for this modulation have been proposed: a fast ephaptic mechanism, and a slow pH mediated mechanism. Here we test the hypothesis that the slow negative feedback signal from horizontal cells to cones is mediated by Panx1 channels expressed at the tips of the dendrites of horizontal cell. We generated zebrafish lacking Panx1 and found that the slow component of the feedback signal was strongly reduced in the mutants showing that Panx1 channels are a fundamental part of the negative feedback pathway from horizontal cells to cones.